Outcome of pregnancies with severe IUGR detected by ultrasound scan at or before 24 weeks. (18th April 2012) - Sankaran, S; Mullins, E; Story, L; Kumar, S; Kyle, PM
Abstract : Introduction: The aim of this study is to assess the perinatal and maternal outcome when severe growth restriction (Estimated Fetal Weight –EFW </= 3rd centile) was diagnosed by ultrasound before 24 weeks gestation. Methods: This was a retrospective study including cases over 9 year period (2003-2011) in two tertiary centres in London. Cases with estimated fetal weight less than or equivalent to the 3rd centile at or before 24 weeks were identified. Those with chromosomal abnormalities or associated structural abnormalities were excluded. Appropriate cases were identified using fetal medicine and maternity databases. Outcome of pregnancy and neonatal outcome, the incidence of caesarean sections and admission to neonatal unit were studied. Results: In total, 26 cases of severe growth restriction diagnosed before or at 24 weeks were identified. 15/26 (57.7%) were nulliparous women. Pre-eclampsia complicated 5 (19.2%) cases. Uterine Artery and Umbilical Artery Dopplers were abnormal in 69.2% and 61.5% of the cases respectively. Twelve out of 15 (80%) liveborn babies were delivered by caesarean section. Twelve out of 15 (80%) liveborn neonates required neonatal unit admission. One neonate died. Congenital CMV, craniosynostosis and Aortic coarctation were detected postnatally in one case each. Conclusion: When severe IUGR was detected before 24 weeks, more than half of pregnancies resulted in neonatal survival (until discharge). There is an increased incidence of delivery by caesarean section and admission into neonatal unit. Multi centre studies involving larger numbers with long term outcome are required to give more information on prognosis.